Spontaneous B cell hyperactivity in autoimmune-prone MRL mice. - Nijnik, A; Ferry, H; Lewis, G; Rapsomaniki, E; Leung, J; Daser, A; Lambe, T; Goodnow, C; Cornall, R (2006)
The MRL-lpr/lpr mouse strain is a commonly used model of the human autoimmune disease systemic lupus erythematosus (SLE). Although much is known about the contribution of the lpr Fas mutation to B cell tolerance breakdown, the role of the genetic background of the MRL strain itself is less well explored. In this study, we use the MD4 anti-hen egg lysozyme Ig (IgHEL) transgenic system to explore B cell function in MRL+/+ and non-autoimmune mice. We demonstrate that MRL IgHEL B cells show spontaneous hyperactivity in the absence of self-antigen, which is associated with low total B cell numbers but an expansion of the marginal zone B cell population. However, B cell anergy is normal in the presence of soluble lysozyme [soluble hen egg lysozyme (sHEL)], and MRL IgHEL B cells undergo normal elimination in the presence of sHEL when competing with a polyclonal C57BL/6 B cell repertoire. We conclude that B cell hyperactivity may contribute to the autoimmune phenotype of MRL+/+ and MRL-lpr/lpr strains when it initiates antibody responses to rare or sequestered antigens that are below the threshold for tolerance induction, but that there is no B cell intrinsic defect in anergy in MRL mice.